Comparison between Levobupivacaine and Levobupivacaine with Clonidine in Erector Spinae Plane Block in Patients undergoing open Cholecystectomy: A Prospective Randomized Double Blinded Study - Swagatika Sahoo; Suman Chattopadhyay; Sagnik Datta; Debasish Bhar; Asim Kumar Maiti (JK Science)
Background: Erector spinae plane (ESP) block is effective for post-operative analgesia in thoracic and abdominal surgeries. There is minimal experience with clonidine (alpha2 agonist) as an adjuvant to levobupivacaine in ESP block. Objective: The objective of the present study is to compare the duration of postoperative analgesia between levobupivacaine and levobupivacaine with clonidine in open cholecystectomy following ESP block. Material and Methods: One hundred patients, randomly divided into two groups, undergoing open cholecystectomy under general anaesthesia (GA), were given ESP block 20 min before administration of GA. Group L received 19 ml of 0.25% levobupivacaine with 1 ml of normal saline and group LC received clonidine (1.5 mcg/ kg) prepared in 1 ml of normal saline as adjuvant with 19 ml of 0.25% levobupivacaine for ESP block. In the postoperative period, the duration and requirement of analgesia were recorded. Results: Duration of post-operative analgesia in group LC was 595.78 ± 71.5 min compared to 357.2 ± 18.14 min in group L. (p<0.0001). The requirement of analgesic in the first 24 hours was also significantly less in group LC (p<0.0001). Conclusion: Clonidine as adjuvant with levobupivacaine in erector spinae plane block provides longer duration of analgesia and reduces analgesic requirement postoperatively without any significant adverse effects.